2000
DOI: 10.1002/1531-8249(200008)48:2<220::aid-ana12>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

The acute behavioral syndrome of anterior thalamic infarction: A prospective study of 12 cases

Abstract: Using systematic investigations, including neurological and neuropsychological examinations and computed tomography and magnetic resonance imaging analyzed on anatomical maps, we prospectively studied 12 patients (age range, 63+/-19 years) with an isolated anterior thalamic infarct. They had acute, severe, perseverative behavior, which was apparent in thinking, speech, and all memory and executive tasks, combined with increased sensitivity to interference. They also showed superimposition of mental activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
52
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 0 publications
10
52
1
2
Order By: Relevance
“…In human infarct cases with ILn damage and in Korsakoff's syndrome cases there is some evidence of deficits in response memory or related tasks (Mair et al , 2002Holdstock et al 1999;Exner et al 2001). There is also evidence that amnesia is specifically related to damage in the AT and its related pathways (von Cramon et al 1985;Ghika-Schmid and Bogousslavsky 2000;Harding et al 2000). Variability and uncertainty across strategically placed lesions is common both in human cases (Parkin et al 1994;Della Sala et al 1997;Van der Werf et al 2000, 2003Schmahmann 2003) and animal models of diencephalic amnesia.…”
Section: Discussionmentioning
confidence: 99%
“…In human infarct cases with ILn damage and in Korsakoff's syndrome cases there is some evidence of deficits in response memory or related tasks (Mair et al , 2002Holdstock et al 1999;Exner et al 2001). There is also evidence that amnesia is specifically related to damage in the AT and its related pathways (von Cramon et al 1985;Ghika-Schmid and Bogousslavsky 2000;Harding et al 2000). Variability and uncertainty across strategically placed lesions is common both in human cases (Parkin et al 1994;Della Sala et al 1997;Van der Werf et al 2000, 2003Schmahmann 2003) and animal models of diencephalic amnesia.…”
Section: Discussionmentioning
confidence: 99%
“…Memory is severely impaired, but language is relatively spared. In the series of Ghika-Schmid and Bogousslavsky, 27 dysarthria, hypophonia, anomia, and decreased verbal and nonverbal fluency were noted, but comprehension, writing, reading, and repetition were normal. The major clinical feature in all patients, however, was persistent deficits in new learning, as well as apathy.…”
Section: Tuberothalamic Artery Infarctionmentioning
confidence: 93%
“…Comparisons of when thalamic strokes do and do not induce amnesia have consistently found that damage to this tract is the best predictor of memory loss (Von Cramon et al 1985;Ghika-Schmid and Bogousslavsky 2000;Van der Werf et al 2000, 2003bCarrera et al 2004). One of these studies also linked recognition deficits to mammillothalamic tract damage ( Van der Werf et al 2003b).…”
Section: The Anterior Thalamic Nucleimentioning
confidence: 99%